12x-19=3x+27

Simple and best practice solution for 12x-19=3x+27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-19=3x+27 equation:


Simplifying
12x + -19 = 3x + 27

Reorder the terms:
-19 + 12x = 3x + 27

Reorder the terms:
-19 + 12x = 27 + 3x

Solving
-19 + 12x = 27 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-19 + 12x + -3x = 27 + 3x + -3x

Combine like terms: 12x + -3x = 9x
-19 + 9x = 27 + 3x + -3x

Combine like terms: 3x + -3x = 0
-19 + 9x = 27 + 0
-19 + 9x = 27

Add '19' to each side of the equation.
-19 + 19 + 9x = 27 + 19

Combine like terms: -19 + 19 = 0
0 + 9x = 27 + 19
9x = 27 + 19

Combine like terms: 27 + 19 = 46
9x = 46

Divide each side by '9'.
x = 5.111111111

Simplifying
x = 5.111111111

See similar equations:

| (2x+10)=(5x-5) | | -2r=100 | | -2(b+4)+5(5-4b)=61 | | 6(4+t)-4(t+3)= | | -5(r+8)=-78 | | Sin(180-x)=-sinx | | -2(b+4)+5(5-4b)=-61 | | 22=7x+6-3x | | 2n-28=-32+4n | | 3r+5=0 | | 10h-22=48 | | 188.9024=2*3.14*3.2*3.2+2*3.14*3.2*h | | 3(1-5m)-(1+7m)=68 | | 15x+20x=7 | | 41+27= | | 3r-y=0 | | 3.3+10m=7.19 | | 2(x+4)-5(x-3)=18 | | 3=-y+6 | | t*5-4=14 | | 88m^2=3+w | | -6(-3x+6)=90 | | x-2(2x-5)=8 | | 37.50-0.5x=42.75-0.75x | | 15x^2+20x-20=0 | | -109=3-4(8n+4) | | x+82+x+102=180 | | log[2](5x+6)=5 | | 7(t-3)+8t=5(3t+4)-11 | | d+20+0.2d= | | t(x)=11x-725 | | (2x-3)squared=5 |

Equations solver categories